1993
DOI: 10.1002/pro.5560020808
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, characterization, and expression of the β subunit of pig heart succinyl‐CoA synthetase

Abstract: The form of succinyl-CoA synthetase found in mammalian mitochondria is known to be an cub dimer. Both GTPand ATP-specific isozymes are present in various tissues. We have isolated essentially identical complementary DNA clones encoding the 0 subunit of pig heart succinyl-CoA synthetase from both newborn and adult tissues.These cDNAs include a 1.4-kb sequence encoding the cytoplasmic precursor to the fl subunit comprised of 417 amino acid residues including a 22-residue mitochondrial targeting sequence. The cDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The design of the gene is different from one used earlier (37) because the crystal structure showed that a methionine residue inserted before the first residue of the mature ␤-subunit could interfere with catalysis (36). It may be the reason for the reduced specific activity of the enzyme produced in E. coli (37). Modified cDNAs encoding the mature ␣-and ␤-subunits were cloned into a single expression plasmid, each cDNA being placed downstream of a separate T7 promoter.…”
Section: Methodsmentioning
confidence: 99%
“…The design of the gene is different from one used earlier (37) because the crystal structure showed that a methionine residue inserted before the first residue of the mature ␤-subunit could interfere with catalysis (36). It may be the reason for the reduced specific activity of the enzyme produced in E. coli (37). Modified cDNAs encoding the mature ␣-and ␤-subunits were cloned into a single expression plasmid, each cDNA being placed downstream of a separate T7 promoter.…”
Section: Methodsmentioning
confidence: 99%
“…As described under Table II. The sequences are for the mature proteins, assuming that the signal peptides are cleaved at the same position as in G-␤ in pig (22).…”
Section: Sequences Of the ␤-Subunits Of G-scs And A-scs In Highermentioning
confidence: 99%
“…Earlier suggestions that the ␣-subunit is more highly conserved than the ␤-subunit (8,13,22) were based on comparisons of sequences of ␤-subunits that we now know to vary in their specificity. When ␤-subunits of the same specificity are compared, identity of sequence is as high as found in ␣-subunits.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations